ADDRESS TERMS USED BY AUSTRALIANS: A CASE STUDY OF MELBOURNE - Dwi Mawan Karifianto (STAIN Sultan Abdurrahman Kepulauan Riau, 2021)
Abstract The use of address terms is an important and interesting sociolinguistic aspect to be studied. In Australian contexts, there are a number of address terms existing in daily interaction. This case study focuses on how address terms are used by Australians; specifically, 1) how often Australians use the address terms mate, babe, dude, love, buddy, darling, sweetie, and honey/hon in their everyday communication, 2) to whom they mostly use the terms towards, and 3) who is more likely to use the terms between male and female. In this study, the main data collection is survey, with the questionnaires distributed to local Australians around the area of Monash University, Melbourne. The findings suggest that from the eight address terms studied, the most frequently used one in daily interaction is mate, followed by love and dude. Next, those address terms are found to be used for various specific people depending on the closeness of relationships to the speaker. In addition, some terms are usable to address both sexes, while some can be used for certain sex only. Finally, for the speaker of those address terms, mate, buddy, and dude are more popular to use among male participants, while darling, sweetie, honey, babe, and love are more popular among female speakers. The findings in this sociolinguistic study confirm the use of address terms link to feelings and solidarity as suggested by the theory.